2021
DOI: 10.3390/agronomy11102059
|View full text |Cite
|
Sign up to set email alerts
|

Cold Stress during Flowering Alters Plant Structure, Yield and Seed Quality of Different Soybean Genotypes

Abstract: The objective of the study was to evaluate the effect of cold stress at flowering stage on plant structure, yield and chemical composition of seeds of 15 soybean cultivars. The study was conducted in 2019–2020, using the complete randomization method, in three replications. Fifteen soybean cultivars belonging to three maturity groups: early (EC), middle-early (MC) and late (LC) cultivars were included. Weekly cold stress (17/13 °C day/night) was applied at plant flowering stage. In the control treatment, plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…In other trials involving soil acidity and cold treatment of soybean, the HFP was not significantly different (Patinni et al, 2020;Staniak et al, 2021). However, in an experiment with Bradyrhizobium, by inoculation of six soybean cultivars in Serbia, it was shown that FPH and PH were significantly shorter after inoculation but not in all studied genotypes (Miladinović et al, 2021).…”
Section: -29mentioning
confidence: 77%
“…In other trials involving soil acidity and cold treatment of soybean, the HFP was not significantly different (Patinni et al, 2020;Staniak et al, 2021). However, in an experiment with Bradyrhizobium, by inoculation of six soybean cultivars in Serbia, it was shown that FPH and PH were significantly shorter after inoculation but not in all studied genotypes (Miladinović et al, 2021).…”
Section: -29mentioning
confidence: 77%
“…This was clearly seen in the plant image data resulting in a high feature importance for the shape-based features (region properties). This is because cold stress disrupts bio-energetic processes, causes changes in metabolism, and contributes to damage to cellular structures, hence the stunted growth and shriveled leaves (Korkmaz and Dufault, 2001;Staniak et al, 2021). These clear differences in the image data resulted in a distinct classification between cold-stressed watermelon plants from normal ones regardless of the age and variety.…”
Section: Discussion Discrimination Between Stressed and Non-stressed ...mentioning
confidence: 99%
“…As a major environmental factor, cold stress limits where crops can be grown and reduces yields. Cold stress reduced soybean seed yield on average by 24% compared to unaffected plants [ 16 ]. Crops like soybeans, which are native to temperate areas, need warm temperatures for germination, growth, development, and maturation.…”
Section: Influence Of Cold Stress On the Growth And Development Of So...mentioning
confidence: 99%